Clinical evaluation of AusDiagnostics SARS-CoV-2 multiplex tandem PCR assay (2020)
Background In the context of the pandemic, the rapid emergency use authorisation of diagnostic assays for SARS-CoV-2 has meant there are few peer-reviewed published studies of clinical performance of commercial assays. Aims To evaluate the clinical performance of AusDiagnostics respiratory multiplex tandem PCR assay including SARS-CoV-2. Methods We reviewed the results following implementation of AusDiagnostics respiratory multiplex tandem PCR assay including SARS-CoV-2, and compared with an in-house RT-PCR assay at our State Reference Laboratory. Results Initial validation using AusDiagnostics coronavirus multiplex tandem PCR assay including SARS-CoV-2 demonstrated good concordance with the State Reference Laboratory. After implementing the AusDiagnostics respiratory multiplex tandem PCR assay including SARS-CoV-2, we tested 7839 samples. 127 samples in which SARS-CoV-2 was detected using the AusDiagnostics assay were referred for testing at the State Reference Laboratory, with concordant results in 118/127 (92.9%) of samples. After resolution of discrepancies, 125/127 (98.4%) of AusDiagnostics results were determined to be true positive results. Out of 7839 samples tested for SARS-CoV-2 during this period, only 2 tests (0.02%) were indeterminate results. Conclusion The AusDiagnostics respiratory MT-PCR assay is a reliable assay for detection of SARS-CoV-2.